The Impact of Work Family School Conflict on Work Stress in Doctoral Management Students at Mercu Buana University - Muchtadin, Muchtadin; Nurul Sukma Lestari (Social Sciences Insights Journal, 2024)
This research is intended to see the effect of work family school conflict on work stress. The study population was 61 doctoral management students in active status who were members of the whatsapp group "UMB Management Doctoral Association". The number of samples was as large as the study population but only 39 people (63.93%) responded. Simple linear regression is used in data analysis. The result is that work family school conflict has a positive impact on work stress. Suggestions for future researchers to expand the scope of doctoral study programs at other universities. For universities, publications provide relief in carrying out campus activities. For the company, it gives tolerance to employees who are in college. For the family, they actually provide support for their families who work while studying.